Investigation of the anisotropic cyclic damage behavior of selective laser melted AISI 316L stainless steel. Issue 11 (22nd May 2019) - Stern, Felix; Kleinhorst, Jan; Tenkamp, Jochen; Walther, Frank
Abstract: The additive manufacturing technique selective laser melting (SLM) is the most common process for metallic powders. The layer‐by‐layer process allows construction of components with high complex designs compared with conventional process routes. However, the orientation of parts related to the build platform and later to different loading conditions should be taken into account as the process‐induced microstructure and defects creating anisotropic mechanical behavior. To evaluate this influence of the building orientation as well as the process‐induced defects, different fatigue tests were performed on the SLM‐processed austenitic steel AISI 316 L (X2CrNiMo17‐12‐2). The distribution of the process‐induced porosity and, thus, the fatigue behavior is strongly related to the building direction, leading to a reduction of fatigue life for the tested 90° specimens of more than 90%.